Quality control measures and student output in University of Uyo and University of Calabar - Ekaette Emenike Iroegbu; Eno Etudor-Eyo (Journal of Education and Learning (EduLearn), 2020)
The study examines the nature of relationship between quality control measures and student output in University of Uyo and University of Calabar. Two research questions and two hypotheses guided the study. The correlational research design was used for the study. The population comprised 2,967 teaching staff and 11,635 students from University of Uyo and University of Calabar. Simple random sampling technique was used to select 642 teaching staff and 1,232 students from the sampled schools. Two instruments, one being researchers-developed instrument titled “Quality Control Questionnaire (QCQ)” and a documentary analysis checklist titled “Student Output Checklist (SOC)” were used for data collection. The instruments used for data collection were face validated by three experts. The reliability co-efficient of QCQ was determined using the Cronbach Alpha Analysis and a reliability index of 0.81 was obtained. The r-value of Pearson Product Moment Correlation (PPMC) coefficient was used to answer the research questions, while PPMC was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that the quality control on student intake and student engagement significantly relates to student output in University of Uyo and University of Calabar. It was therefore concluded that the quality of student output in University of Uyo and University of Calabar is influenced by quality control variables. Based on the findings of this study, it is therefore recommended amongst others that, universities’ admission regulatory body should ensure that all prospective students vying for admission have good grades in their O’levels and Unified Tertiary Matriculation Examination (UTME). Furthermore, all candidates should also be admitted based on merit in order to ensure quality student output.